Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning Di Kelas V Tema 3 Subtema 2 Pembelajaran 1 SD Negeri 105322 Desa Mesjid - Hanum, Mayva (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this research was to improve student learning outcomes by using the Problem-based learning model on theme 3, sub-theme 2, learning 1 with the subject matter characteristic of electronic media advertisements and digestive organ disorders in class V SD Negeri 105322 Desa Mesjid, academic year 2022/2023. This type of research is Classroom Action Research, with the research subject being Class V students at SD Negeri 105322 Desa Mesjid for the 2022/2023 academic year. There are 19 students, with details of 7 male students and 12 female students. This research was carried out in two learning cycles. With 4 (four) stages in each cycle, namely planning, implementation, observation/observation, and reflection. The data collection tools are tests and observation sheets. Based on the initial tests conducted, it was found that of the 19 students who took the pre-test, there were 7 students who completed the learning outcomes with a percentage of 37% and 12 students who had not completed the pre-test with an average percentage of 63% with an average of 59. ,4. Researchers followed up in cycle I by using the Problem based learning learning model on theme 3 sub-themes 2 learning 1 subject matter features of electronic media advertising and digestive organ disorders, the acquisition of cycle I results increased to 11 students who completed learning outcomes with a percentage of 58% and there were 8 students incomplete with a percentage of 42% with an average classical score of 71. Based on the temporary conclusion, that student learning outcomes have not been as expected or have not reached a good classical completeness percentage level, so it needs improvement and development in cycle II. In cycle II, the acquisition of student learning outcomes increased to 16 students who completed their learning outcomes with a percentage of 84% and not yet completed 3 students with a percentage of 16% with an average classical score of 83.